2008
DOI: 10.1177/1468794108093898
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the `field': multiple standpoints, narrative and shifting positionality in multisited research

Abstract: The article contributes to the epistemological debates in feminism through the analysis of multisited research on jewellery production in India. The multisited research focuses on different localities -Noida Export Processing Zone (NEPZ), Delhi and villages of Medinipur having direct and indirect links to the global market. It analyses how the multiple sites structured by gender, class and age hierarchies reveal the multiple and fluid standpoints of different actors. The multiple standpoints of different actor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In this instance it is evident that I was performing multiple 'roles' and occupying multiple 'positions', the combination of which raises ethical implications for the data utilized and the argument outlined in this article (Soni-Sinha, 2008). This tripartite positionality, facilitator/former prisoner/researcher, coupled with my mixed ethnicity, gender and social class (what Earle (2013: 18) has referred to as the 'persistent trialities of social science'), afforded me a great deal of personal access and enabled prisoners to 'open up' about their issues and experiences in ways they may not have if my 'cultural competence' (Hodkinson, 2005: 138) was not recognized, if there were not some shared experiences and the acknowledgement that our role there was to help improve the lives of those who inhabited the prison.…”
mentioning
confidence: 99%
“…In this instance it is evident that I was performing multiple 'roles' and occupying multiple 'positions', the combination of which raises ethical implications for the data utilized and the argument outlined in this article (Soni-Sinha, 2008). This tripartite positionality, facilitator/former prisoner/researcher, coupled with my mixed ethnicity, gender and social class (what Earle (2013: 18) has referred to as the 'persistent trialities of social science'), afforded me a great deal of personal access and enabled prisoners to 'open up' about their issues and experiences in ways they may not have if my 'cultural competence' (Hodkinson, 2005: 138) was not recognized, if there were not some shared experiences and the acknowledgement that our role there was to help improve the lives of those who inhabited the prison.…”
mentioning
confidence: 99%
“…Several qualitative researchers have demonstrated interest in studying up to the elite and how this affects access (Becker and Aiello 2013;Conti and O'Neil 2007;Forsythe 1999;Ho 2012;Nader [1969Nader [ ] 1972Shore 2002). Among scholars using qualitative field methods, attending to the researcher's position illuminates her simultaneous positions as both an insider and an outsider within the field site (Casper 1997;Merton 1972;Soni-Sinha 2008;Traweek 1992;Turgo 2012aTurgo , 2012b and how accessing the field site influences research results (Casper 1997;Turgo 2012a). Only a few scholars have considered the ethnographer's multiple hierarchical status positions in comparison to her or his interlocutors (Bowman 2009;Hannerz 2006;Nader [1969Nader [ ] 1972Reinhold 1994).…”
mentioning
confidence: 99%
“…Positionality, particularly in sociological terms, is talked about in the context of the inherent power structures that are embedded within our social, political, economic, and ideological systems in relation to others with whom we human beings share this world (Anthias, 2002;Martin & Gunten, 2002;Milner, 2007;Muhammad et al, 2015;Relles, 2016;Soni-Sinha, 2008). Specifically, the power structures referred to in this study are central to white-identified individuals and their experiences within the context of selfidentifying as white, as opposed to individuals who identify as POC (Anthias, 2002;Brewer & Heitzeg, 2008;Martin & Gunten, 2002;Milner, 2007;Muhammad et al, 2015;Relles, 2016;Soni-Sinha, 2008;Tillery, 2009).…”
Section: Positionality and The Construction Of Whitenessmentioning
confidence: 99%
“…Positionality, particularly in sociological terms, is talked about in the context of the inherent power structures that are embedded within our social, political, economic, and ideological systems in relation to others with whom we human beings share this world (Anthias, 2002;Martin & Gunten, 2002;Milner, 2007;Muhammad et al, 2015;Relles, 2016;Soni-Sinha, 2008). Specifically, the power structures referred to in this study are central to white-identified individuals and their experiences within the context of selfidentifying as white, as opposed to individuals who identify as POC (Anthias, 2002;Brewer & Heitzeg, 2008;Martin & Gunten, 2002;Milner, 2007;Muhammad et al, 2015;Relles, 2016;Soni-Sinha, 2008;Tillery, 2009). These imbalanced systemic power relations are evident in networks of crime and punishment, educational (in)equity, healthcare accessibility, and good, viable jobs-and the ways that societal advantages are allocated to white-identified communities as opposed to those of POC identity (Brewer & Heitzeg, 2008;Dache-Gerbino & White, 2016; T. L. Green & Dantley, 2013;Manglitz, 2003;Staurowsky, 2007;Todd, Suffrin, McConnell, Odahl-Ruan, 2015;& van Gorder, 2007).…”
Section: Positionality and The Construction Of Whitenessmentioning
confidence: 99%
See 1 more Smart Citation